2020
DOI: 10.20944/preprints202012.0783.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Schizophrenia, Depression and Anxiety Symptoms Are Driven by Immune-Inflammatory Pathways.

Abstract: Background. The aim of this study is to examine whether biomarkers of the immune-inflammatory response (IRS) and endogenous opioid (EOS) systems are associated with affective symptoms in schizophrenia. Methods. We recruited 115 schizophrenia patients and 43 healthy controls and assessed the Hamilton Depression (HDRS) and Anxiety (HAM-A) rating Scale scores as well as serum levels of interleukin (IL)-6, IL-10, eotaxin (CCL11), high mobility group box 1 (HMGB1), Dickkopf-related protein 1 (DKK1), and mu (MOR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…The study by Chen et al also confirmed elevated HMGB1 levels in patients with a 1st episode of schizophrenia compared with healthy controls, and after 8 weeks of treatment, the study group's HMGB1 levels decreased significantly; however, they continued to be elevated [106]. In schizophrenia, symptoms of depression and anxiety are driven by immune and inflammatory pathways, wherein HMGB1 plays an important role [107]. According to Al-Hakeim et al, schizophrenic patients responding only partially to treatment, in whom complete remission of the disease cannot be observed following treatment, have increased HMGB1 levels.…”
Section: Hmgb1 In Psychiatrymentioning
confidence: 81%
“…The study by Chen et al also confirmed elevated HMGB1 levels in patients with a 1st episode of schizophrenia compared with healthy controls, and after 8 weeks of treatment, the study group's HMGB1 levels decreased significantly; however, they continued to be elevated [106]. In schizophrenia, symptoms of depression and anxiety are driven by immune and inflammatory pathways, wherein HMGB1 plays an important role [107]. According to Al-Hakeim et al, schizophrenic patients responding only partially to treatment, in whom complete remission of the disease cannot be observed following treatment, have increased HMGB1 levels.…”
Section: Hmgb1 In Psychiatrymentioning
confidence: 81%